DONORS OF COMMERCIALLY VALUABLE TRAITS FOR SWEET CHERRY BREEDING - E. M. Alekhina; L. D. Chalaya; T. G. Prichko (Вавиловский журнал генетики и селекции, 2015)
Long-term studies of frost resistance, merchantability, and contents of biologically active compounds in new promising and recommended sweet cherry varieties grown in Krasnodar krai are reported. Frost-resistant varieties valuable for breeding are outlined. Varieties rich in biologically active compounds have been found. Their use in breeding programs will increase the pool of vitamins in fruit of new hybrid accessions.